Pengaruh Kualitas Sumber Daya Manusia Terhadap Pengelolaan Dana Desa Dalam Peningkatan Pertumbuhan Ekonomi Masyarakat: Kualitas Sumber daya manusia, Pengelolaan dana desa,Pemberdayaan ekonomi desa, Pembangunan desa berbasis SDM, Faktor Penghambat dan Pendukung Pengelolaan Dana Desa - Sutra Ridena Koesherawaty Meylid; Dwi Putri Yuliani (Jurnal Perlindungan Masyarakat: Bestuur Praesidium, 2024)
This article aims to describe the quality of human resources in the management of village funds to empower the village economy and to identify factors that enable and hinder the process, from managing village funds to the quality of human resources in the village. The article employs a literature study method. The literature study approach is used to investigate the role of human resource quality and village fund management in the context of rural development. Relevant literature on human resource quality, village fund management, and rural economic growth serves as the basis for identifying factors influencing economic growth at the village level. Fundamentally, a country's progress can be identified through the development of its villages. Therefore, human resources play a crucial role in the village fund management process to foster economic growth. The case study focuses on a village that is analyzed in-depth, with an emphasis on the implementation of human resource quality and village fund management in local economic development. The findings reveal that high-quality human resources, particularly in terms of education and skills, have a positive impact on village fund management and economic growth. Community empowerment, income diversification, and the use of technology are identified as critical factors in this success. Keywords: Human Resource Quality, Village Fund Management, Village Economic Empowerment, Human Resource-Based Village Development, Inhibiting and Supporting Factors in Village Fund Management.